Total Suspended Particulate and Impaired Lung Function at Operators of Public Fuel Filling Stations in Mamuju Regency - Haeranah Ahmad; Fajar Akbar; Askur Askur (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
The transportation sector plays a major role in air pollution in urban areas. Operators of Public Fuel Filling Stations are at risk of inhaling pollutants from motor vehicle emissions such as CO, NO, SO2 and dust particulates. The objective of this study is to determine the relationship of Total Suspended Particulate (TSP) to the occurrence of impaired lung function at SPBU operators. This type of research is observational with a cross sectional study design with sampling technique using total sampling on the entire population, which is performing lung function examinations on 34 operators at three gas stations in Mamuju Regency. Examination of lung function used spirometry while the measurement of total dust concentration used a High Volume Air Sampler (HVAS). Data analysis was performed using the Chi-square test. The results showed that there was no significant relationship between TSP levels and impaired pulmonary function. Even though TSP exposure levels did not have a significant relationship with lung pulmonary function, efforts to control dust exposure were still necessary because most respondents worked in a working environment with high TSP levels. The results of this study are expected to be a reference for the implementation of health and safety programs for workers and the implementation of working environment monitoring and occupational health surveillance.